Menkes Disease- A Rare Neurodegenerative Disorder - Choudhary, Richa; Choudhary, Anita; Sitaraman, S (Journal of Nepal Paediatric Society, 2016)
Menkes Disease is a rare neurological disorder of impaired copper transport, characterized by progressive neurodegeneration, refractory epilepsy and characteristic hair abnormalities. Here, we report a 5 month old child with developmental delay, refractory seizures, and hypopigmented short, sparse hair with microscopic pili torti; low serum copper and ceruloplasmin and neuroimaging revealing white matter hyperintensities and tortuous vessels. J Nepal Paediatr Soc 2015;35(2):177-180